SISTEM INFORMASI INVENTARISASI PERALATAN MEDIS PADA RUMAH SAKIT BUAH HATI CIPUTAT - Naufal Rafly Pamungkas (2023)
Technology has become a very important role in helping all activities. With technology, it can simplify and speed up the activities of an institution or business. One of the institutions that utilize technology is the hospital. Buah Hati Ciputat Hospital is a professional health care institution that has a variety of services. With the number of patients, medical equipment for patient care needs must be added. Currently, the management of medical equipment at the Buah Hati Ciputat Hospital is still using Microsoft Excel, so the possibility of duplication, errors, and data corruption is very possible. So that a computerized and integrated web-based inventory system is needed to record all services performed on medical equipment management so it has accurate transaction data and prevents data duplication, errors, and data corruption. The system design method used is waterfall and PIECES for the analysis method. The PIECES analysis method is used to analyze existing problems, by identifying existing problems regarding information system performance, economy, security, efficiency and service for users. The programming language used for system development is PHP and MySQL for the database. the conclusion of this study is that it can simplify the process of making inventory reports at Buah Hati Ciputat Hospital, and can also upload application letters without the printing process so as to reduce paper use significantly. The purpose of developing this system is to be able to assist in the process of managing medical equipment at the Buah Hati Ciputat Hospital.